2003
DOI: 10.1007/s00464-002-8528-0
|View full text |Cite
|
Sign up to set email alerts
|

Removal of esophageal expandable metal stents

Abstract: The safe removal of current brands of EMS may facilitate the wider application of these devices to include selective patients with benign disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Leaving stents in place long term in patients whose life expectancy is not limited is considered to be inappropriate and potentially dangerous [9]. We have previously published a report documenting the feasibility of safe SEMS removal [12]. It is clear, however, that this process can be associated with significant risk.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Leaving stents in place long term in patients whose life expectancy is not limited is considered to be inappropriate and potentially dangerous [9]. We have previously published a report documenting the feasibility of safe SEMS removal [12]. It is clear, however, that this process can be associated with significant risk.…”
Section: Discussionmentioning
confidence: 97%
“…Removal of the SEMS has been described [12]. However, the difficulty and potential danger associated with their removal has significantly limited their application for benign patients apart from sporadic reports of their use in highly selected patients with esophageal perforation [13].…”
mentioning
confidence: 99%
“…Since the 1990s, esophageal intubation with stent prostheses has gradually developed. Several types of covered expandable metallic stents have been used with higher rates of complete closure of TEF, which can avoid certain complications, such as hemorrhage, perforation, pressure necrosis, food impaction, stent dislocation, occlusion, and migration [3], [11], [12], [13], [14], [15]. In Taiwan, feeding gastrostomy/jejunostomy and stenting have become the most common treatment modalities for TEF.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Although recent studies reported the usefulness of SEMSs for the treatment of benign esophageal stricture,26,27,28 potential late-onset complications are related to long-term stent placement. 26 , 27 , 28 , 29 , 30 Moreover, there is no removal mechanism in currently available SEMSs, which may result in difficult stent removal after long-term placement. Currently, no consensus on the appropriate duration of SEMS placement exists.…”
Section: Post-esd Stricture In the Esophagusmentioning
confidence: 99%
“…In previous studies, the duration of SEMS placement varied from 3 days to several months. 26 , 27 , 28 , 29 However, no report on SEMS placement for the treatment of post-ESD cicatricial stricture has existed until now. To overcome the difficulty in removing stents, the use of self-expanding Polyflex plastic stents (Willy Ruesch GMBH, Kernen, Germany), 25 fully covered retrievable SEMSs, 31 or biodegradable stents 32 , 33 has been suggested.…”
Section: Post-esd Stricture In the Esophagusmentioning
confidence: 99%